Effects of the Shape and Size of Irregular Particles on Specific Breakage Energy under Drop Weight Impact - Deqing Gan; Feng Gao; Yunpeng Zhang; Jinxia Zhang; Fusheng Niu; Ze Gan (Shock and Vibration)
Particle shape and size are main factors influencing particle breakage. Single-particle breakage tests were conducted on irregular magnetite ore using modified drop weight impact equipment to analyze the effect of shape and size on specific breakage energy. A method to measure the effective breakage energy is presented. Ore particles with different sphericities and different sizes were broken into several fragments with differing impact energies in the tests. Experimental studies indicate that the shape of particles significantly influences the impact loading mode and breakage progress; the specific breakage energy has an obvious relationship with the sphericity and the initial size. The specific breakage energy decreases with larger initial loading area. The particle needs less specific breakage energy if the shape or placement state is more conducive to tensile fracture. There is an increase in specific breakage energy corresponding to an increase in particle sphericity with fixed initial size range. With the increase in the initial size of the particle, the specific breakage energy decreases with fixed sphericity range, which presents a power function with the exponent −0.5. The comprehensive relationship between specific breakage energy, particle sphericity, and initial size was established, showing that the input power of the crushing machinery and the optimization of crushing technology should be performed with consideration of the influence of particle shape and initial size to reduce specific energy consumption and improve energy efficiency.